The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1525-1497.2005.40052.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol screening in young persons attending a sexually transmitted disease clinic

Abstract: OBJECTIVE:To compare the ability of 3 brief alcohol screens (Alcohol Use Disorders Identification Test [AUDIT], CRAFFT, and CAGE) to identify adolescents and young adults with a current alcohol use disorder (AUD) and to determine whether there are gender-based or race-based differences in screening performance. DESIGN, PARTICIPANTS, AND SETTING:Cross-sectional study of 358 young persons (55% males; 49% blacks; age range, 15-24 years; mean age, 20.6 years) who were attending an urban clinic for sexually transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 35 publications
0
81
0
9
Order By: Relevance
“…REV BRAS EPIDEMIOL JAN-MAR 2015; 18(1): [13][14][15][16][17][18][19][20][21][22][23][24] No significant differences among analyzed variables from students of peripheral and central schools were found (data not shown), and for this they formed the urban group [n = 557; 306/555 (55.1%) girls; two students did not inform their gender]; sociodemographic characteristics are described in Table 1. In total, 1,012 (61.3%) of the invited students did not participate in the study by reason of not bringing the signed informed consent form, absence to classes in days of questionnaire administration, and one student was not authorized by the mother.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…REV BRAS EPIDEMIOL JAN-MAR 2015; 18(1): [13][14][15][16][17][18][19][20][21][22][23][24] No significant differences among analyzed variables from students of peripheral and central schools were found (data not shown), and for this they formed the urban group [n = 557; 306/555 (55.1%) girls; two students did not inform their gender]; sociodemographic characteristics are described in Table 1. In total, 1,012 (61.3%) of the invited students did not participate in the study by reason of not bringing the signed informed consent form, absence to classes in days of questionnaire administration, and one student was not authorized by the mother.…”
Section: Resultsmentioning
confidence: 99%
“…AUDIT was developed by the World Health Organization (WHO), consists of 10 questions, and classifies individuals as to alcohol use in low risk or abstinence (score 0 -7), risk consumption (score 8 -15), harmful consumption (score 16 -19), and probable alcohol dependence (score ≥ 20) 18 . This tool has been validated for the Brazilian population 19 and has good sensitivity (0.76) and specificity (0.79) for the identification of risk consumption (score ≥ 8) among adolescents 20 . The questionnaires were applied by one of the authors (TGR), and students had privacy for filling the questionnaire and took on average 20 minutes for this.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a threshold score of 2 of 6, some studies have found that CRAFFT has acceptable sensitivity and specificity for identifying adolescents likely to have AUDs or other substance use disorders (eg, sensitivity, 0.80; specificity, 0.86; positive predictive value, 0.53; and negative predictive value, 0.96). 10 However, other studies have found that CRAFFT has poor specificity (0.33 in the study by Cook et al 12 and 0.44 in the study by Kelly et al 13 ). The advantages of CRAFFT include a broadened screening focus to the inclusion of "drugs," the interview format, and simple response options (yes or no).…”
Section: Screening For Underage Drinking and Audsmentioning
confidence: 64%
“…15 Studies of older adolescents (ie, >18 years) have found that a threshold score of 8 has yielded acceptable results on both sensitivity and specificity. 12,13 We recommend a threshold of 3 to maximize sensitivity of the scale for use in adolescents younger than 18 years. For those aged 18 through 20 years, a threshold of 8 is recommended.…”
Section: Screening For Underage Drinking and Audsmentioning
confidence: 99%